Nano-Sonosensitized Sonodynamic Nanomedicine Augments Tumor-Selective Catalytic Tumor Eradication - Zhang, Haixian; Li, Yiming; Liu, Junying; Chang, Cai (Frontiers in Materials, 2022)
Inspired by the distinct metabolic pathway of tumor cells, here a new anti-cancer therapy (i.e., Cu-TCPP(Fe) metal-organic frameworks (MOFs) with sonosensitizer for sonodynamic therapy (SDT) and tumor microenvironment (TME)-specific release of copper/iron for chemical catalysis is introduced and verified. Upon exposure to ultrasound, the porphyrin structure in the MOFs yields reactive oxygen species (ROS), and the copper/iron induces the Fenton reaction in the TME existing H2O2 and acid. Thus, highly toxic ROS are generated through these TME-specific reactions to trigger the apoptosis and death of tumor cells. The current work paves a new avenue to design SDT with catalytic nanomedicine for the selective and effective treatment of tumors.